Metastatic involvement of level IIb nodal station in oral squamous cell carcinoma: A clinicopathological study - Chakraborty, Partha S. (Natl J Maxillofac Surg, 2019)
BACKGROUND: The purpose of this study was to determine the prevalence of Level IIb metastasis in patients with oral squamous cell carcinomas (OSCCs). MATERIALS AND METHODS: A total of 110 newly diagnosed oral cavity cancer patients requiring surgery as the primary modality were included in the study. Preoperative clinical examinations were done and tumor-node-metastasis staging was noted. Intraoperatively, Level IIb nodal tissue was dissected and sent separately. RESULTS: A total of 129 neck dissections (58 SOHD, 67 modified neck dissections, and 4 radical neck dissections) were carried out in 110 patients (males = 80 and females = 30), 91 patients required unilateral neck dissection, and 19 patients required bilateral neck dissection. Out of these 129 neck dissections, only 4 (3.2%) neck dissections (in a total of 3 patients out of 110 patients) had Level IIb positive (with bilateral Level IIb involvement in one patient). CONCLUSIONS: Dissection of the Level IIb region in patients with OSCC may be required only in cases with advanced N stage, positive Level IIa lymph nodes, and extracapsular spread. Furthermore, in tongue cancers (high propensity of isolated Level II involvement), retromolar trigone, and floor of mouth cancers, routine Level IIb clearance should be considered.